2012
DOI: 10.1371/journal.pgen.1002738
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-Containing DNA in Drosophila: Stability, Stage-Specific Accumulation, and Developmental Involvement

Abstract: Base-excision repair and control of nucleotide pools safe-guard against permanent uracil accumulation in DNA relying on two key enzymes: uracil–DNA glycosylase and dUTPase. Lack of the major uracil–DNA glycosylase UNG gene from the fruit fly genome and dUTPase from fruit fly larvae prompted the hypotheses that i) uracil may accumulate in Drosophila genomic DNA where it may be well tolerated, and ii) this accumulation may affect development. Here we show that i) Drosophila melanogaster tolerates high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 49 publications
5
97
1
2
Order By: Relevance
“…Uracil incorporation into DNA was measured using a qPCR-based assay following the protocol described by Horváth and Vértessy (2010) with minor variations (20,21). Cq values obtained were used to determine uracil content as described (20).…”
Section: Quantitative Determination Of Uracil In Dnamentioning
confidence: 99%
“…Uracil incorporation into DNA was measured using a qPCR-based assay following the protocol described by Horváth and Vértessy (2010) with minor variations (20,21). Cq values obtained were used to determine uracil content as described (20).…”
Section: Quantitative Determination Of Uracil In Dnamentioning
confidence: 99%
“…The elevation of uracil content was observed in almost all tissues investigated, except the embryo. 28 We suggest that this phenomenon is due to lack of the gene encoding the catalytically competent UNG enzyme from the Drosophila genome.…”
Section: Holometabola Insectsmentioning
confidence: 92%
“…We investigated genomes of other insects and found that Holometabola are usually similar in this respect, all those organisms where annotated genomes are already available seem to lack UNG. 30 The immediate suggestion is that genomic uracil content in these insects is also elevated in a similar developmental pattern. This implies that dUTPase levels are under developmental either prokaryotic or eukaryotic organisms, studied previously.…”
Section: Holometabola Insectsmentioning
confidence: 99%
See 2 more Smart Citations